Mindful Kangaroo Care: mindfulness intervention for mothers during skin-to-skin care: a randomized control pilot study - Marc-Antoine Landry; Kumar Kumaran; Juzer M. Tyebkhan; Valerie Levesque; Marcello Spinella (BMC, 2022)
Abstract Background Parents of babies admitted to the Newborn Intensive Care Unit (NICU) undergo considerable stress. There is evidence that mindfulness reduces stress in these parents. Kangaroo Care (KC) is practiced in NICUs across the world and is stress-relieving. Whether mindfulness practiced during KC in the NICU reduces parental distress has not yet been studied. The objective was to explore the feasibility and acceptability of teaching and practicing mindfulness during KC for mothers of premature babies. The objective was also to document preliminary outcomes of Mindful Kangaroo Care (MKC) on maternal stress, anxiety, depression, and mindful awareness. Methods In this pilot randomized controlled study, mothers of premature babies who were expected to stay in the NICU for at least four weeks were taught two mindfulness exercises to practice during KC and compared to mothers who received standard care with no mindfulness teaching. Mothers filled out stress, anxiety, depression and mindful awareness scales at recruitment and after four weeks. Acceptability and feasibility questionnaires were also completed. Results Fifteen mothers per group completed the study. The MKC group demonstrated a significant within-group reduction in anxiety (p = 0.003), depression (p = 0.02) and stress (p = 0.002), and a significant increase in both the curiosity (p = 0.008) and decentering (p = 0.01) scores of the Toronto Mindfulness Scale, all of which had medium to large effect sizes. Only the increases in curiosity and decentering were significant between groups. Fourteen mothers found the intervention acceptable, one neutral. Conclusion MKC was acceptable, feasible and led to a reduction in stress, anxiety and depression in mothers who practiced mindfulness exercises during KC.